Identificación de los peligros y puntos críticos de control en la producción cavícola del Centro Experimental y de Producción Salache (CEYPSA). Propuesta de un sistema de seguridad alimentaria y ambiental para mejorar la producción de cuyes. - Andrade Aulestia, Patricia Marcela (2013)
This research focuses on the identification of hazards and critical control points in the production cavícola Experimental Center and Salache Production. The objectives were to: Identify the scientific and technical foundations that ensure quality production in guinea pigs and Production Experimental Centre Salache; Determine the environmental, food, health management and production of CEYPSA cavícola ; Perform analysis hazards and critical control points ( HACCP ) in the guinea pig production CEYPSA and create a proposal for a system of environmental and food safety to enhance production of CEYPSA guinea pigs . The theoretical framework incorporates content on the guinea pig husbandry characteristics and technical aspects for breeding, and the principles of the Hazard Analysis and Critical Control Point. The proposal corresponds to a feasible project, supported by field research and literature. The research procedure was: documentary information collection, field work, making the diagnosis of the current situation, exploitation characterization of guinea map development risk, hazard analysis and critical control points, making conclusions and recommendations and proposal development. Once identified hazards and critical control points were established a surveillance system, corrective action and verification system based on them. Finally, we present a proposal for a system of Food and Environmental Safety which aims to help improve guinea pig production in the Experimental and Production Center Salache.